2015
DOI: 10.1039/c4em00619d
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change and socio-economic scenarios on flow and water quality of the Ganges, Brahmaputra and Meghna (GBM) river systems: low flow and flood statistics

Abstract: The potential impacts of climate change and socio-economic change on flow and water quality in rivers worldwide is a key area of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 30 publications
1
67
0
Order By: Relevance
“…However, using the INCA-N, an inland catchment modelling system and considering the projected climatic and socioeconomic scenarios, Whitehead et al (2015) showed that there would be a significant increase in future monsoon intensities due to the impact of climate change. That would make future flooding scenarios much worse than those experienced presently.…”
Section: Discussionmentioning
confidence: 99%
“…However, using the INCA-N, an inland catchment modelling system and considering the projected climatic and socioeconomic scenarios, Whitehead et al (2015) showed that there would be a significant increase in future monsoon intensities due to the impact of climate change. That would make future flooding scenarios much worse than those experienced presently.…”
Section: Discussionmentioning
confidence: 99%
“…Inputs of freshwater at river mouths in the GBM delta area were provided using outputs from a hydrological model of the river basins 33,34 : these were created using the same HadRM3P Q0, Q8 and Q16 climate forcing data as the Bay of Bengal model. The GBM rivers provide 40% of the modelled freshwater flow into the entire domain and dominate in the delta area.…”
Section: Riversmentioning
confidence: 99%
“…The fits to the Ganges flow data are of a similar order of magnitude (Whitehead et al 2015a). In addition to calibrating the flow model, it is necessary to calibrate the water quality model.…”
Section: Climate Drivers For the Gbm Riversmentioning
confidence: 59%